A stable dual-wavelength Q-switch using a compact passive device containing photonics crystal fiber embedded with carbon platinum - Safaei, R.; Amiri, Iraj Sadegh; Rezayi, Majid; Ahmad, Harith (IOP Publishing, 2017)
A compact fiber laser utilizing platinum nanoparticles doped on carbon (Pt/C) embedded in photonic crystal fiber capable of generating a stable Q-switch dual-wavelength is designed and verified. Stable Q-switch pulses, with a repetition rate of 73.6 kHz, pulse width of 1.45 μs and power of 3.8 nJ in two separated wavelengths of 1557.39 nm and 1558.86 nm at a pump power of 350 mW, have been obtained. This is a novel method for generating Q-switch dual-wavelength pulses using a well-protected component that introduces both a saturable absorber and Mach-Zehnder interferometer effects simultaneously in the laser cavity. Furthermore, to best of our knowledge, this is the first time that Pt/C nanoparticles have been used in a saturable absorber for optical pulse generation.